2018
DOI: 10.1055/s-0037-1620268
|View full text |Cite
|
Sign up to set email alerts
|

Risks of Preterm Premature Rupture of Membranes and Preterm Birth Post Fetoscopy Based on Location of Trocar Insertion Site

Abstract: We found that trocar insertion in the LUS, particularly the lateral LUS, was associated with an increased risk of PPROM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Previous studies have found that vaginitis caused by infection is a risk factor for premature rupture of membranes [ 46 , 47 ]. One possible reason is that infection leads to the destruction of the glial fibers of the membranes, which reduces the toughness of the membranes and increases the risk of PROM.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that vaginitis caused by infection is a risk factor for premature rupture of membranes [ 46 , 47 ]. One possible reason is that infection leads to the destruction of the glial fibers of the membranes, which reduces the toughness of the membranes and increases the risk of PROM.…”
Section: Discussionmentioning
confidence: 99%